Hippocampal morphometry in sudden and unexpected death in epilepsy. (20th August 2019) - Somani, Alyma; Zborovschi, Anita-Beatrix; Liu, Yan; Patodia, Smriti; Michalak, Zuzanna; Sisodiya, Sanjay M.; Thom, Maria
Abstract : Objective: To determine hippocampal morphometric measures, including granule cell dispersion and features of malrotation, as potential biomarkers for sudden unexpected death in epilepsy (SUDEP) from an archival postmortem series. Methods: In a retrospective study of 187 archival postmortems from 3 groups, SUDEP (68; 14 with hippocampal sclerosis [HS]), non-SUDEP epilepsy controls (EP-C = 66; 25 with HS), and nonepilepsy controls (NEC = 53), Nissl/hematoxylin & eosin–stained sections from left and right hippocampus from 5 coronal levels were digitized. Image analysis was carried out for granule cell layer (GCL) thickness and measurements of hippocampal dimensions (HD) for shape (width [HD1], height [HD2]) and medial hippocampal positioning in relation to the parahippocampal gyrus (PHG) length (HD3). A qualitative evaluation of hippocampal malrotational (HMAL) features, dentate gyrus invaginations (DGI), and subicular/CA1 folds (SCF) was also made. Results: GCL thickness was increased in HS more than those without ( p < 0.001). In non-HS cases, increased GCL thickness was noted in EP-C compared to NEC ( p < 0.05) but not between SUDEP and NEC. There was no difference in the frequency of DGI, SCF, measurements of hippocampal shape (HD1, HD2, or ratio), or medial positioning among SUDEP, EP-C, and NEC groups, when factoring in HS, coronal level, and age at death. Comparison between left and right sides within cases showed greater PHG lengths (HD3) on the right side in the SUDEP group only ( p = 0.018). Conclusions: No hippocampal morphometric features were identified in support of either excessive granule cell dispersion or features of HMAL as definitive biomarkers for SUDEP. Asymmetries in PHG measurements in SUDEP warrant further investigation as they may indicate abnormal central autonomic networks.